Immunolocalization of myosin Va in the developing nervous system of embryonic chicks - Azevedo, Alexandre [UNESP]; Lunardi, Laurelúcia O.; Larson, Roy E. (Springer, 2004)
Myosins are molecular motors associated with the actin cytoskeleton that participate in the mechanisms of cellular motility. During the development of the nervous system, migration of nerve cells to specific sites, extension of growth cones, and axonal transport are dramatic manifestations of cellular motility. We demonstrate, via immunoblots, the expression of myosin Va during early stages of embryonic development in chicks, extending from the blastocyst period to the beginning of the fetal period. The expression of myosin Va in specific regions and cellular structures of the nervous system during these early stages was determined by immunocytochemistry using a polyclonal antibody. Whole mounts of chick embryos at 24-30-h stages showed intense immunoreactivity of the neural tube in formation along its full extent. Cross-sections at these stages of development showed strong labeling in neuroepithelial cells at the basal and apical regions of the neural tube wall. Embryos at more advanced periods of development (48h and 72 h) showed distinctive immunolabeling of neuroepithelial cells, neuroblasts and their cytoplasmic extensions in the mantle layer of the stratified neural tube wall, and neuroblasts and their cytoplasmic extensions in the internal wall of the optic cup, as well as a striking labeling of cells in the apparent nuclei of cranial nerves and budding fibers. These immunolocalization studies indicate temporal and site-specific expression of myosin Va during chick embryo development, suggesting that myosin Va expression is related to recruitment for specific cellular tasks.
Keywords: Chick development; Embryo; Myosin Va; Neural tube; myosin; polyclonal antibody; biological marker; myosin heavy chain; myosin V; animal tissue; blastocyst; cell labeling; cell migration; cell motility; cell nucleus; cell structure; chicken; cranial nerve; cytoplasm; cytoskeleton; developmental stage; embryo development; immunoblotting; immunocytochemistry; immunolocalization; immunoreactivity; nerve fiber; nervous system development; neural tube; neuroblast; neuroepithelium; nonhuman; optic disk cup; priority journal; protein expression; animal; antibody specificity; biosynthesis; cell differentiation; chick embryo; cytology; epithelium cell; eye; gene expression regulation; immunohistochemistry; metabolism; nerve cell; nervous system; physiology; prenatal development; Animals; Antibody Specificity; Biological Markers; Cell Differentiation; Chick Embryo; Cranial Nerves; Epithelial Cells; Eye; Gene Expression Regulation, Developmental; Immunohistochemistry; Myosin Heavy Chains; Myosin Type V; Nervous System; Neurons